1982
DOI: 10.1107/s0567740882003392
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure and crystal packing analysis of triphenylchloromethane

Abstract: IntroduetlonC19H15C1 is trigonal, space group P3, with a = 13.998 (2), c = 13.202 (4)/k, V = 2240.2 A 3, Z = 6, Dm= 1.26, D x = 1.240 Mg m -3, F(000) = 876,/~ = 0.225 mm-k The final R and R w, based on 905 reflections, are 0.038 and 0.025 respectively. The molecules lie in special positions on the crystallographic threefold axes. They are associated in pairs and form two distinct Ph3C-C1...CI-CPh 3 head-to-head arrangements characterized by long C-C1 bonds and short C1... CI contacts. The shortest C1... C1 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…[17] To our knowledge, no other crystal structures of chlorinated hydrocarbons with such short Cl···Cl separations between chlorine atoms involved in highly elongated C À Cl bonds (above 1.85 ) have ever been reported. Recently, we have found that the chlorine atoms in the structure of C 76 Cl 18 form a number of extremely short Cl···Cl contacts of about 3.14-3.21 , [3] which are about 0.45 shorter than the sum of the van der Waals radii.…”
Section: Resultsmentioning
confidence: 96%
“…[17] To our knowledge, no other crystal structures of chlorinated hydrocarbons with such short Cl···Cl separations between chlorine atoms involved in highly elongated C À Cl bonds (above 1.85 ) have ever been reported. Recently, we have found that the chlorine atoms in the structure of C 76 Cl 18 form a number of extremely short Cl···Cl contacts of about 3.14-3.21 , [3] which are about 0.45 shorter than the sum of the van der Waals radii.…”
Section: Resultsmentioning
confidence: 96%
“…Crystallographically equivalent TPBM and TPCM molecules have very similar overall geometries; in particular, the distortions from tetrahedral angular symmetry at the central Cc atom are equal within experimental error (average C-Cc-C and Ci-Cc-X angle values 112.3 and 106-5 °, respectively). The internal steric interactions already detailed for TPCM (Dunand & Gerdil, 1982) are equally operative in TPBM. The dihedral angles between the phenyl mean planes and the plane through the C-C-Br fragment are 51.1, 46.6 and 44.0 °, respectively.…”
Section: Molecular Geometrymentioning
confidence: 93%
“…The present study is a natural extension to our recent investigation of the crystal structure and crystal packing of triphenylchloromethane (Dunand & Gerdil, 1982). Triphenylchloromethane (TPCM) and triphenylbromomethane (TPBM) crystallize in isomorphous systems and both structures display linear head-to-head C-X.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such short Cl···Cl contacts cannot be explained by the close packing of anisotropic building units. [14] We regard the short contacts as evidence of unconventional attractive interaction between the chlorine atoms.…”
Section: Methodsmentioning
confidence: 99%